Transition Metal Aluminum Boride as a New Candidate for Ambient-Condition Electrochemical Ammonia Synthesis - Fu, Yang; Richardson, Peter; Li, Kangkang; Yu, Hai; Yu, Bing; Donne, Scott; Kisi, Erich; Ma, Tianyi (Nano-Micro Letters, 2020)
Achieving more meaningful N2 conversion by reducing the energy input and carbon footprint is now being investigated through a method of N2 fixation instead of the Haber–Bosch process. Unfortunately, the electrochemical N2 reduction reaction (NRR) method as a rising approach currently still shows low selectivity (Faradaic efficiency < 10%) and high-energy consumption [applied potential at least − 0.2 V versus the reversible hydrogen electrode (RHE)]. Here, the role of molybdenum aluminum boride single crystals, belonging to a family of ternary transition metal aluminum borides known as MAB phases, is reported for the electrochemical NRR for the first time, at a low applied potential (− 0.05 V versus RHE) under ambient conditions and in alkaline media. Due to the unique nano-laminated crystal structure of the MAB phase, these inexpensive materials have been found to exhibit excellent electrocatalytic performances (NH3 yield: 9.2 µg h−1 cm−2 mg−1cat., Faradaic efficiency: 30.1%) at the low overpotential, and to display a high chemical stability and sustained catalytic performance. In conjunction, further mechanism studies indicate B and Al as main-group metals show a highly selective affinity to N2 due to the strong interaction between the B 2p/Al 3p band and the N 2p orbitals, while Mo exhibits specific catalytic activity toward the subsequent reduction reaction. Overall, the MAB-phase catalyst under the synergy of the elements within ternary compound can suppress the hydrogen evolution reaction and achieve enhanced NRR performance. The significance of this work is to provide a promising candidate in the future synthesis of ammonia. Highlights: 1 Molybdenum aluminum boride single crystals as layered ternary borides were firstly applied for the electrochemical N2 reduction reaction under ambient conditions and in alkaline media, displaying excellent electrocatalytic performances at the low overpotential. 2 Through the combination of the strong interaction of Al/B band and N orbitals and the special crystal structure exposing more active sites, synergistic effect of the elements was verified to achieve the enhancement of N2 reduction reaction process and the limitation of hydrogen evolution reaction.